Torchwood : rift war - Furman, Simon; Grist, Paul; Edginton, Ian; Williamson, Brian (Titan Books, 2009)
Torchwood follows the adventures of a team of investigators, working for the secret organization, who use scavenged alien technology to solve present day crimes - both alien and human.